When to invest in high-speed rail links and networks? - Chris Nash (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
Definitions of high speed rail (HSR) differ, but a common one is rail systems which are designed for a maximum speed in excess of 250 kph (UIC, 2008). These speeds invariably involve the construction of new track, although trains used on them can also use existing tracks at reduced speeds. A number of countries have upgraded existing track for higher speed, with tilting technology on routes with a lot of curves. However such trains do not normally run at speeds above 200 km p h. Their rationale is to upgrade services at relatively low cost in countries which have sufficient capacity to cope with increased divergence of speeds on routes shared with all forms of traffic. Most of the countries which adopted this strategy initially, such as Britain and Sweden, are now considering building HSR. The only form of totally new technology that has come close to being implemented is maglev.
Keywords: 330